1990
DOI: 10.1017/s0074180900187637
|View full text |Cite
|
Sign up to set email alerts
|

Balmer and soft X-ray emission from solar and stellar flares

Abstract: Integrated soft X-ray (8-12A) fluxes for solar flares have been scaled to the equivalent EXOSAT fluxes using spectra obtained from a variety of rocket-based experiments. The data show good agreement with the soft X-ray - Hγ correlation established by Butler et al. (1988) for stellar flares and confirm the basic similarity, in this respect, of flares on the Sun to those on dMe stars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…On M dwarfs we are not able to measure proton events, but we can use X-rays as a proxy, at least for the most intense flares. This is supported by observations that show that solar flares and active M dwarfs obey common relationships (Butler et al 1988). Belov et al (2005) found that solar X-ray flare intensity can be quantitatively related to proton fluxes: I p (>10MeV) = (4.8±1.3) × 10 7 I x 1.14±0.14…”
Section: Input Proton Flux and Nitrogen Oxides Productionmentioning
confidence: 56%
“…On M dwarfs we are not able to measure proton events, but we can use X-rays as a proxy, at least for the most intense flares. This is supported by observations that show that solar flares and active M dwarfs obey common relationships (Butler et al 1988). Belov et al (2005) found that solar X-ray flare intensity can be quantitatively related to proton fluxes: I p (>10MeV) = (4.8±1.3) × 10 7 I x 1.14±0.14…”
Section: Input Proton Flux and Nitrogen Oxides Productionmentioning
confidence: 56%